The Heme Degradation Pathway is a Promising Serum Biomarker Source for the Early Detection of Alzheimer's Disease - Mueller, Claudius; Zhou, Weidong; VanMeter, Amy; Heiby, Michael; Magaki, Shino; Ross, Mark M.; Espina, Virginia; Schrag, Matthew; Dickson, Cindy; Liotta, Lance A.; Kirsch, Wolff M. (Journal of Alzheimer's disease, 2010)
One of the remaining challenges in Alzheimer's disease (AD) research is the establishment of biomarkers for early disease detection. As part of a prospective study spanning a period of five years, we have collected serial serum samples from cognitively normal, mild cognitively impaired (MCI), and mild AD participants, including same patient samples before and after cognitive decline. Using mass spectrometry we identified several promising leads for biomarker development, such as prosaposin, phospholipase D1, biliverdin reductase B, and S100 calcium binding protein A7. Selected candidate markers were verified using reverse phase protein microarray assays. Of 15 protein/protein abundance ratios that were significantly altered in sera from subjects with mild AD compared to Normal or MCI subjects, 14 were composed of ratios containing heme oxygenase-1, biliverdin reductase A, or biliverdin reductase B. Moreover, an increase in the protein abundance ratio of matrix metallopeptidase 9/biliverdin reductase differentiated stable MCI subjects from MCI subjects progressing into mild AD before the onset of cognitive decline. These findings strongly implicate the heme degradation pathway as a promising source of protein biomarkers for the early detection of AD.